Transformative Learning through Technology: How Google Sites-Enhanced Projects Foster Creative Thinking in Geography? - Heni Farhatin, Safelly; Putra, Alfyananda Kurnia; Riwanti, Lintang Ayu; Mkumbachi, Ramadhani Lausi (Future Space: Studies in Geo-Education, 2024)
Project-based learning (PjBL) is a problem-oriented learning model as the beginning of combining new knowledge with experience. The advantages of the PjBL model are able to spur students in creative thinking and can increase students to understand the theory learned along with creativity in applying their understanding to a project. The application of the PjBL model requires a variety of learning media that helps students in the process of collaboration and exploration, namely through google sites. This study aimed to determine the effect of PjBL, facilitated by Google Sites, on students' creative thinking in geography education. The study employed a quasi-experimental design, using an independent T-test to analyze the impact of PjBL on creative thinking skills. The research subjects included students from classes X-8 and X-9 at State Senior High School 7 Malang, selected based on purposive sampling to ensure similar baseline characteristics. The results and discussion show that project-based learning assisted by google sites is able to encourage students' creative thinking, especially those related to fluent thinking. It was proven by the acquisition of Independent Sample T test value Sig. (2-tailed) of 0.040 <0.05. Thus, it can be said that the project-based learning model assisted by google sites in geography subjects affects students' creative thinking skills. The findings include: 1) students are very active and enthusiastic during the learning process, 2) female students have better creative thinking skills than male students.